2014
DOI: 10.1039/c3ta15090a
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase synthesis of a Li3PS4 solid electrolyte using N-methylformamide for all-solid-state lithium batteries

Abstract: A Li 3 PS 4 solid electrolyte was directly synthesized from Li 2 S and P 2 S 5 by a liquid-phase reaction using N-methylformamide (NMF) and n-hexane as reaction media. After the reaction of Li 2 S and P 2 S 5 , a yellow NMF solution was obtained. The NMF solution was dried at 180 C for 3 hours under vacuum to remove NMF and to obtain a powder. A crystalline phase of the obtained powder from the NMF solution was attributed to Li 3 PS 4 crystals, and the ionic conductivity of the obtained powder was 2.3 Â 10 À6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 23 publications
4
116
0
Order By: Relevance
“…Thus, the electron density of oxygen atom will take the important role in the synthetic process and the reactivity of the solvents is expected to be in this order DMC > EA > MPK. In the liquid-phase synthesis process, the products directly precipitated from the solvents were reported to be the co-crystalline of solid electrolytes and solvents [9][10][11][12] . It is also reported that the bonds between solid electrolytes and solvents originated from Li ion of the electrolytes and C=O group in solvents.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the electron density of oxygen atom will take the important role in the synthetic process and the reactivity of the solvents is expected to be in this order DMC > EA > MPK. In the liquid-phase synthesis process, the products directly precipitated from the solvents were reported to be the co-crystalline of solid electrolytes and solvents [9][10][11][12] . It is also reported that the bonds between solid electrolytes and solvents originated from Li ion of the electrolytes and C=O group in solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Atsunori MATSUDA, Hiroyuki MUTO and Nguyen H.H. PHUC N-methylformamide (NMF), in which the reaction between NMF and P 2 S 5 was proved to be the initial step [9][10][11][12]15) . Thus, the electron density of oxygen atom will take the important role in the synthetic process and the reactivity of the solvents is expected to be in this order DMC > EA > MPK.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations